Preclinical model of obesity based on ultra-processed and highly palatable foods - Quesada, Dayana (2021)
Introduction: The alarming increase in obesity both worldwide and in Costa Rica is mainly due to changes in the composition of the usual diet of the population. The goal of our research was to implement a feeding protocol formulated from ultra-processed and highly palatable foods (UPHP) consumed by the Costa Rican population and to evaluate the effects of the UPHP diet on eating behavior and biometric and biochemical parameters. Methods: Adult male Wistar rats were assigned to two groups. One group was given standard rodent chow (DC group) while the other group received UPHP foods (UPHP group) for eight weeks. Results: Throughout this period, animals exposed to the UPHP diet exhibited higher food and energy intake characterized by high consumption of fat and lower consumption of protein and fiber. Animals in the UPHP group also showed a significant increase in obesity parameters (e.g., body weight and bodyweight gain, Lee's index, and central adiposity). Furthermore, the UPHP group had descriptively higher levels of blood glucose and triglycerides and significantly lower levels of total cholesterol. Conclusions: Our results indicate that a feeding protocol based on the most frequent food choices of the Costa Rican population is capable of inducing hyperphagia and obesity. This model constitutes a promising tool to delve into the study of the neurobiological and metabolic factors related to obesity induced by overconsumption of UPHP foods.